Comparison of anaerobic efficiency rating in football players groups of age range 12 - 14 and 17 - 18 years based on Wingate test - Fortuna, M.; Socha, G.; Szczurowski, J.; Zemelko, J.; Demczyszak, I. (Journal of Education, Health and Sport, 2018)
One of the features shaped in football training along with aerobic fitness is anaerobic capacity. Speed is closely related to the genotype, developmental age and especially to the level of training. Aim: The aim was to compare the rate of anaerobic effciency in grups of football players of age range 12-14 and 17-18 based on Wingate test. Material and methods: We compared 36 football players 12-14 years old and 28 football players 17-18 years old. Grups of respondents rated: time and power level to obtain the maximum duration of maximum power and the rate of decline in power. During the tests, the height and weight of the athletes were measured and the BMI was calculated. Results and conclusions: Maximum power level and the rate of decrease in power in the treated grups showed no significant differences. Arithmetic average time to obtain and maintain maximum power are statistically significant. The level of training of players has a significant impact on the formation of anaerobic capacity. The 12-14-year-old footballers, on the basis of better sport preparation, obtained a comparable, high level of maximum power and a shorter time of achieving it in comparison with the results of 17-18-year-old players. In football players aged 17-18, a longer time of maintaining the maximum power was noted, which indicates a higher non-lactic anaerobic capacity in this group compared to the group of younger players. Lack of significant differences in the power drop index compared to the tested groups indicates similar possibilities related to the glycolytic capacity. For all somatic parameters tested, the players from the 17-18 age category are characterized by significantly higher values of the mean parameters tested.